Prerequisites for Transference of Professional Football Clubs in Iran with Emphasis on Economic Requirements - Nahid Atghia; Hassan Gharehkhani; Somaye Yaghoubi (Shahid Bahonar University of Kerman, 2021)
Transference of professional sports clubs to private sector involves the necessary conditions for private sector activity. Therefore, the aim of this study was to determine the prerequisites for the transference of professional football clubs in Iran with emphasis on economic requirements. Statistical population included all CEOs and members of board of directors from professional football clubs, chairmen of committees and officials of provincial football boards, sports management and economics professors as well as football reporters. The research tool was a valid and reliable researcher-developed questionnaire. Factor analysis and Friedman ranking test were employed to analyze the research data. According to the results, the prerequisites for privatization were categorized in seven factors including cultural, executive, programming, motivational, legal, economic, and structural. Moreover, economic requirements (4.20) were the most important category, followed by executive (4.14), structural (4.04), motivational (4.02), legal (3.99), programming (3.97), and cultural requirements (3.62), respectively. Among the economic requirements, the transparency of financial information from country's football clubs, presence of strong sponsors and the creation of supportive funds for financial guarantee of private sector are in the first to third ranks, respectively. According to the findings the most important priority is to solve the financial problems and revenue generation of the clubs.